(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Oxidative stress in mammals results from imbalance between generation of free radicals and the rate of their suppression by antioxidant. Hepatotoxicity may result as an effect of excessive free radical formation due to exogenous chemicals or metabolic reactions. D-Galactosamine (D-GalN) is a well known hepatotoxicant. Herbal medicines have been utilized to manage hepatotoxicity according to recent trends. In the present study Herbal Preparation or HP-4 is a combination of 80% alcoholic extract of leaves of Aloe vera, Bacopa monniera, Moringa oleifera and rhizome of Zingiber officinale has been utilized to study its efficacy on mice model of D-GalN hepatotoxicity. D-GalN hepatotoxicity induces liver injury closely resembling human viral hepatitis with necrosis, inflammation and regeneration. Evidenced by biochemical and histopathological studies it is concluded that polyherbal formulation HP-4 offered a synergistic protection due to the phytochemicals present which provide hepatoprotective activity induced by D-GalN hepatotoxicity.